2023
DOI: 10.3390/molecules28052091
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatoria limnetica Mediated Green Synthesis of Iron Oxide (Fe2O3) Nanoparticles and Their Diverse In Vitro Bioactivities

Abstract: Iron oxide nanoparticles (Fe2O3-NPs) were synthesized using Oscillatoria limnetica extract as strong reducing and capping agents. The synthesized iron oxide nanoparticles IONPs were characterized by UV-visible spectroscopy, Fourier transform infrared (FTIR), X-ray diffractive analysis (XRD), scanning electron microscope (SEM), and Energy dispersive X-ray spectroscopy (EDX). IONPs synthesis was confirmed by UV-visible spectroscopy by observing the peak at 471 nm. Furthermore, different in vitro biological assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Hassan et al (2022) produced green-synthesized FeO NPs with an average diameter of 31.45 nm, which were observed using SEM to illustrate the dimensions and morphology of the mostly spherical NPs [111]. Haris et al (2023) investigated the geometry of biosynthesized FeO NPs using SEM and confirmed the presence of trigonal rhombohedral crystalline forms, which is consistent with the XRD findings. The formation of distinct shapes in large particles can be attributed to the crystal development process.…”
Section: Scanning Electron Microscopy (Sem)-energy Dispersive X-ray S...supporting
confidence: 53%
See 1 more Smart Citation
“…Hassan et al (2022) produced green-synthesized FeO NPs with an average diameter of 31.45 nm, which were observed using SEM to illustrate the dimensions and morphology of the mostly spherical NPs [111]. Haris et al (2023) investigated the geometry of biosynthesized FeO NPs using SEM and confirmed the presence of trigonal rhombohedral crystalline forms, which is consistent with the XRD findings. The formation of distinct shapes in large particles can be attributed to the crystal development process.…”
Section: Scanning Electron Microscopy (Sem)-energy Dispersive X-ray S...supporting
confidence: 53%
“…The examination conducted using EDX analysis provided qualitative and quantitative information regarding the presence and concentration of Fe components involved in the production of FeONP. Absorption peaks were observed in the energy range of 6-7 keV as a result of the surface plasmon resonance exhibited by Fe NPs [119].…”
Section: Scanning Electron Microscopy (Sem)-energy Dispersive X-ray S...mentioning
confidence: 99%
“…Another study reported the successful synthesis of Fe 2 O 3 -NPs from Oscillatoria limnetica . Researchers reported significant antibacterial activities of Fe 2 O 3 -NPs against MDR E. coli , S. aureus , and B. subtilis [ 24 ]. Likewise, Fe 2 O 3 -NPs were produced effectively by utilizing gum extract from Bombax malabaricum .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cyanobacteria Leptolyngbya valderiana [ 29 ], Leptolyngbya sp. WUC 59 [ 30 ], Nostoc ellipsosporum [ 31 ], Anabaena flos-aquae and Calothrix pulvinata [ 32 ] Oscillatoria limnetica [ 33 ] were employed for the biogenic synthesis of FeONPs. Oscillatoria limnetica and Desertifilum sp.…”
Section: Introductionmentioning
confidence: 99%